Local elections in the Republic of Serbia 2016 and 2020: Political consequences of lowering the electoral threshold - Perišić Nikola; Kaličanin Boris (Srpska Politička Misao)
The paper examines the political consequences of the change in electoral legislation through a comparative analysis of election results at the local level in 2016 and 2020. In addition to the analysis of the election results themselves, and bearing in mind the boycott of the majority of the opposition in the 2020 elections, the paper will also show a simulation of the election results of 2016 with a reduced electoral threshold of 3% in order to better understand the effect of lowering the electoral threshold, considering that at that time all relevant political parties participated in local elections. The electoral results from cities that are the seat of administrative districts (24) in the Republic of Serbia, excluding the city of Belgrade and Kosovo and Metohija, are used as a sample for the analysis. The main findings of the research show that the lowering of the electoral threshold did not increase representativeness. More precisely, the number of lists represented in local parliaments did not increase, neither in absolute nor in effective numbers. However, the impact of the boycott of the opposition parties in the 2020 election process should be taken into account. On the other hand, the analysis shows that a larger number of lists would have crossed the electoral threshold if the three-percent electoral threshold had been applied in 2016. In addition, in 2020, a smaller number of so-called "wasted votes" was observed. Lastly, lowering the electoral threshold did not help the citizens groups to achieve better election results in 2020.